Piroplasm infestations in cattle: exploring tick control using Chrysanthemum extract and neem oil emulsion - Abd-Elrahman, Salwa Mahmoud; Kamel, Fatma Atea; Abdel-Hakeem, Sara Salah; Khedr, Abeer A.; Mohamed, Shaymaa M.; Abdelgaber, Ahmed A.; Darwish, Madeha; Al-Hakami, Ahmed M.; Alqahtani, Abdulah J.; Dyab, Ahmed Kamal (Frontiers in Veterinary Science, 2025)
IntroductionTick-borne diseases represent a major threat to both animal and human health globally. This study explores the prevalence of tick infestation and associated piroplasm infections specifically Theileria and Babesia species in cattle, in addition to evaluating the acaricidal effectiveness of Chrysanthemum extract (Dendranthema grandiflora) and neem oil emulsion (Azadirachta indica).MethodsAmong 130 cattle examined, 61 were infested with ticks and subsequently screened for piroplasm infections. Molecular analysis identified infections caused by Theileria annulata and Babesia bigemina.ResultsA strong association was found between tick infestation and Babesia species, while T. annulata infection showed a slight correlation. Hemolymph examination confirmed the critical role of ticks in the life cycle of piroplasm infection. Chrysanthemum extract and neem oil were tested for their acaricidal properties against adult ticks (Rhipicephalus annulatus). Chrysanthemum extract (0.5 mg/mL) caused tick mortality within 24 h. However, neem oil induced rapid and significant tick mortality at (20 mg/L) and (15 mg/L), achieving 100% mortality within the same time frame. Both treatments demonstrated high effectiveness, with results indicating strong dose-and time-dependent effects compared to controls. Scanning electron microscopy (SEM) revealed extensive morphological damage to treated ticks. This damage included destruction of the hypostome, loss of surface striations, wrinkling with pore formation, and cracking following exposure to neem oil and Chrysanthemum extract.DiscussionThese findings highlight the potential of D. grandiflora extract and neem oil emulsion as effective natural acaricides for controlling tick infestations and reducing tick-borne diseases.